Hands-On Full Stack Web Development with Aurelia Develop Modern and Real-Time Web Applications with Aurelia and Node. js - Argüelles Rojas, Diego (Packt Publishing Ltd, 2018)
Isomorphic JavaScript has been a buzzword lately, allowing developers to utilize a single language throughout their web development stack and build cost-effective and scalable applications. This book is on one such modern web development stack which comprises of web technologies like MongoDB, Express.js, Aurelia.js, and Node
Description based on publisher supplied metadata and other sources
Keywords: Network analysis (Planning)